Memahami “Noun” Bahasa Inggris untuk Menentukan Lead Term dalam Mengkode Diagnosis Mengunakan ICD-10 Volume 3 - Rahmi Septia Sari (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Based on the importance of codification, a coder must improve their knowledge and their skills.,one of the skill is to improve their English language skill both oral and written. A coder must understand English because  English is one of the languages on ICD-10. There are some steps of coding patient’s disease, one of them is to determine the lead term. Understanding Noun  in English is one alternative way for coder to simplify determining the lead term. This study aims to (1) To understand the characteristics of Noun, (2) To indentify and classify Noun on ICD -10 Volume 3 and (3) To analyze Noun on ICD-10 Volume 3. Maethod of this study is descriptive qualitative study that is devided into three steps they are: preparing the study, collecting data and analyzing the data. The result shows that the type and characteristics of noun can be found on ICD-10 Volume 3 and based on its function, noun is the sentence head. Noun is the lead term for coding diseases with ICD-10 and Noun on ICD-10 volume 3 are mostly lead terms except common noun relating to parts of body.